Establishing a personalized information security culture - Talib, Shuhaili; Clarke, Nathan L.; Furnell, Steven M. (IGI Global, 2011)
Good security cannot be achieved through technical means alone and a solid understanding of the issues and how to protect one’s self is required from users. Whilst many initiatives, programs and strategies have been proposed to improve the level of information security awareness, most have been directed at organizations. Given people’s use of technology is primarily focused between the workplace and home; this paper seeks to understand the knowledge and practice relationship between these environments. Through a developed survey, it was identified that the majority of the learning about information security occurred in the workplace, where clear motivations, such as legislation and regulation, existed. Results found that users were more than willing to engage with such awareness raising initiatives. From a comparison of practice between work and home environments, it was found that this knowledge and practice obtained at the workplace was transferred to the home environment. Given this positive transferability of knowledge and the willingness to learn about how to remain secure, an opportunity exists to move away from specific organizational awareness programs and to move towards awareness raising strategies that will develop an all-round individual security culture for users independent of the environment they are operating in.